Efecto del consumo de harina de maíz fortificada con ácido fólico sobre los niveles de folatos sanguíneos en mujeres de edad fértil - Sánchez P., Maria Alejandra; Esmer Sánchez, María del Carmen; Martínez de Villarreal, Laura Elia; Varela G., Nadia; Valdez L., Ramón; Torres Sepúlveda, María del Rosario; López O., Rocío; Villarreal Pérez, Jesús Zacarías (2011)
Fortification of foods is now widely used to prevent folate deficiency. Folic acid has been added to corn flour and its efficacy in the prevention of NTD has been proved. The aim of this study was to compare the effect of the intake of fortified corn-flour versus non fortified flour and to folic acid supplement, on blood folate levels in women of childbearing age. Forty-five women were randomized into three groups according to: (A) use of fortified flour (n=18), (B) non-fortified flour (n=17); (C) supplementation with 5 mg of oral folic acid (n=10). All females answer a dietary and anthropometric questionnaire applied once a month during three months. Blood red cell (IE) and plasmatic (P) folate were measured at the beginning and at the end of the study; also the DNA analysis for the 677T mutation was performed. The corn flour was provided to groups A and B during three months, to be consumed as eight tortillas daily. Group C received 5.0 mg tablet of folic acid (Valdecasas®), once per week, during three months. IE and P folate and hematocrito were significantly increased in women from group C (p<0.05) ). Only plasmatic folic acid levels were significantly increased in women from groups A and B. Genotype distribution was: 15.6% homozygous TT, 42.2% C/C and 42.2% CT. Weekly administration of 5.0 mg of folic acid is an effective way to increase blood folate levels and shows to be more efficient than fortified corn flour.